Peran Komunikasi Keluarga Dalam Pembentukan Identitas Sosial Anak (Studi di Desa Kertajaya Kecamatan Padalarang Bandung Barat) - Syanni, Kevin Firdaus; Sidharta, Veranus (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The process of forming social identity does not occur automatically; it isinfluenced by various factors, one of which is communication within the family.Family communication plays a crucial role in shaping children's social identity.Through effective communication, families can help children develop self-confidence, social skills, and an understanding of the norms of social life. Thisresearch aims to analyze the role of family communication in the formation ofchildren's social identity, identify factors that influence the effectiveness ofcommunication within the family, and provide practical recommendations forparents and educators in supporting the development of children's social identitythrough effective communication. The research employs a qualitative approach.The findings indicate that the social identity of children in Kertajaya Village,Padalarang District, West Bandung, is shaped by traditional family structures, theparents' profession—primarily as teachers—and daily interactions that includesocial support, empathy, and openness. Parents' roles as teachers enable them toeducate their children both at school and at home, integrating educational valuesand discipline into the household.